Penentuan Kriteria Pembentukan Kelompok Tani dalam Pengelolaan Kerja Sama UMKM Kopi - Andri Ikhwana; Qonita Aini Fajrianti (Institut Teknologi Garut, 2022)
This study aims to determine the supporting criteria for the formation of cooperation and the financial feasibility of forming coffee farmer groups in Garut Regency. This study uses a quantitative descriptive methodology. Primary and secondary data are used in this study. Primary data were obtained through direct observation and interviews with coffee farmers in Garut Regency using the Analytic Hierarchy Process (AHP) and Hayami approaches. In order to find out the farmer's decision to determine the criteria in the formation of cooperation, the highest criteria weight was obtained, namely management, production, capital, and sustainable environmental monitoring. Business feasibility in the process of caring for trees up to the sale of grain in each farmer group (Mulyabakti Sukamanah, Berkahtani, and Muda Mandiri) that the profitability/profits obtained are 74%, and 3%. If the level of profit or profitability is > 0%, the business being run is profitable. Then the added value obtained from Mulyabakti Sukamanah is 63%, Berkahtani is 62%, and Muda Mandiri is 61%. Finally, the percentage of compensation for labor at Mulyabakti Sukamanah is 26%, Berkahtani is 26%, and Muda Mandiri is 97%. The results of this study indicate that farmers' decisions in forming farmer groups affect the financial feasibility of coffee farmers in Garut Regency.